The Catholic Church and Liberal Democracy - Oftestad, Bernt Torvild, author.
1 online resource (226 pages)
Keywords: The Roman Catholic Church's critical stance towards liberalism and democracy following the French Revolution and through the19th century was often entrenched, but the Second Vatican Council of the 1960s saw a shift in the Church's attitude towards democracy. In recent years, a conflict has emerged between Church doctrine and modern liberalism under Popes John Paul II and Benedict XVI. This book is a comprehensive overview of the Catholic Church's relationship to modern liberal democracy, from the end of the 18th century until today. It is a connection that is situated within the context of the history of ideas itself.